Surface engineering of poly(methyl methacrylate)–reduced graphene oxide composite films by Au7+ ion irradiation for biomedical application. (June 2022) - Ramya, J. Ramana; Arul, K. Thanigai; Ilangovan, R.; Sathiamurthi, P.; Asokan, K.; Dong, Chung-Li; Arockiarajan, A.; Kalkura, S. Narayana
Abstract: In this work, PMMA-reduced graphene oxide (rGO) films (PrGO) were prepared by solvent evaporation and further, swift heavy ions (100 MeV gold ion) irradiated on them by varying fluences viz. 1 × 10 11, 5 × 10 11 and 1 × 10 12 ions/cm 2 (referred as PrGO-111, PrGO-511, PrGO-112). There was a low angle peak shift of rGO and the reduction of crystallinity at higher fluences. On irradiation, the intensities of the vibrational modes of C–H bonding, hydroxyl, carboxyl groups of rGO and the band gap (36%) are reduced. The surface roughness (69%), pore size (∼10–24 μm), hemocompatibility and contact angle are enhanced on irradiation. The antibacterial efficiency and cell proliferation were augmented on PrGO-511 compared to the other films. The Au ion irradiation tailors surface roughness, contact angle, antibacterial activity and cell proliferation. Further, the atomic local bonding and surface roughness are correlated with the biological properties. Thus, the irradiated PrGO films could be an excellent candidate for applications in the biomedical field. Highlights: First report on 100 MeV Au ions irradiation on PMMA/rGO film. Atomic disorder and bonding of films are tailored on irradiation. Enhanced surface roughness (69%) and wettability (17%) achieved on irradiation. Antimicrobial, cell viability and proliferation of irradiated films are improved.